Evolutionary analysis of the female-specific avian W chromosome - Smeds, Linnéa; Warmuth, Vera; Bolivar, Paulina; Uebbing, Severin; Burri, Reto; Suh, Alexander; Nater, Alexander; Bureš, Stanislav; Garamszegi, Laszlo Z; Hogner, Silje; Moreno, Juan; Qvarnström, Anna; et al. (Nature communications, 2015)
The typically repetitive nature of the sex-limited chromosome means that it is often excluded from or poorly covered in genome assemblies, hindering studies of evolutionary and population genomic processes in non-recombining chromosomes. Here, we present a draft assembly of the non-recombining region of the collared flycatcher W chromosome, containing 46 genes without evidence of female-specific functional differentiation. Survival of genes during W chromosome degeneration has been highly non-random and expression data suggest that this can be attributed to selection for maintaining gene dose and ancestral expression levels of essential genes. Re-sequencing of large population samples revealed dramatically reduced levels of within-species diversity and elevated rates of between-species differentiation (lineage sorting), consistent with low effective population size. Concordance between W chromosome and mitochondrial DNA phylogenetic trees demonstrates evolutionary stable matrilineal inheritance of this nuclear-cytonuclear pair of chromosomes. Our results show both commonalities and differences between W chromosome and Y chromosome evolution.
Keywords: molekulární evoluce; pěnkavovití; Lizards; Finches; Sex Chromosomes; Struthioniformes; pohlavní chromozomy; želvy; ještěři; DNA, Mitochondrial; Birds; Turtles; kur domácí; plazi; Animals; ženské pohlaví; Chickens; zvířata; Reptiles; zpěvní ptáci; mitochondriální DNA; fylogeneze; Songbirds; ptáci; Female; Phylogeny; Evolution, Molecular